Assessing the impact of sports and recreation facility density within school neighbourhoods on Canadian adolescents’ substance use behaviours: quasi-experimental evidence from the COMPASS study, 2015–2018 - Scott T Leatherdale; Amanda Doggett; Katelyn M Godin; Olena Schell; Suzy L Wong (BMJ Open)
Objectives There has been relatively little exploration to date of potential protective effects within school neighbourhoods, such as those conferred by facilities that seek to promote health with respect to substance use and related harms. This study examined how the density of sports and recreation facilities in the school neighbourhood is associated with the likelihood of binge drinking, e-cigarette use, cigarette smoking and cannabis use among Canadian secondary school students.Design Longitudinal data from the COMPASS study on Canadian youth health behaviours from 2015/2016 to 2017/2018 was linked with school neighbourhood data capturing the number of sports and recreation facilities within a 1500 m radius of schools.Setting Secondary schools and school neighbourhoods in Alberta, British Columbia, Ontario and Quebec who participated in the COMPASS study.Participants 16 471 youth who participated in the COMPASS study over three school years (2015/2016–2017/2018).Primary and secondary outcome measures Binge drinking, e-cigarette use, cigarette use, cannabis use.Results Logistic regression models using generalised estimating equations identified that greater density of sports and recreation facilities within the school neighbourhood was significantly associated with lower likelihood of binge drinking and e-cigarette use but was not associated with cigarette smoking or cannabis use.Conclusions This research can help to support evidence-informed school community-based efforts to prevent substance-related harms among youth.